Genomic Analysis of Halophilic Ureolytic Bacteria and its Applications in Sustainable Construction Materials - Gautam, Shivangi (Thapar Institute of Engineering and Technology, 2025)
Environmental salinity poses a significant challenge to sustainable construction particularly in coastal and arid regions where conventional building materials degrade faster. In the present study, a halophilic ureolytic bacterium, Bacillus paramycoides MD6 was evaluated for its potential in Microbially Induced Calcium Carbonate Precipitation (MICCP) under saline conditions. The isolate exhibited high Urease activity (up to 599 U/mL at 2.5% NaCl) and Carbonic anhydrase activity (105 U/mL at 0% NaCl followed by 2.5% - 102 U/mL and 3.5%- 90 U/mL), both of which declined at increasing salt concentrations indicating that moderate salinity supports optimal enzymatic performance. The bacterium also demonstrated effective Calcium carbonate (CaCO3) precipitation (maximum 195 mg at 0% NaCl followed by 2.5% and 3.5%) which confirmed its ability to biomineralize even under mild salt stress. Mortar cubes treated with MD6 culture showed enhanced compressive strength (up to 28.3 ± 0.7 MPa) and reduced water absorption (0.073 g/cm2 ) indicating improved durability. Wholegenome analysis revealed the presence of key genes for urease, carbonic anhydrases and wide range of salt tolerant genes. These findings suggest that B. paramycoides MD6 is a promising candidate for environmentally friendly and durable bio-construction in saline environments.
M.Sc. thesis
Keywords: Biomineralization; MICCP; Bioconcrete; Halophilic Bacteria; Sustainable Construction; Genomic Analysis; Ureolytic Bacteria